Pain Catastrophizing Thoughts Explain the Link Between Perceived Caregiver Responses and Pain Behaviors of Patients With Chronic Musculoskeletal Pain - Mohammadi, Somayyeh; Alinajimi, Fatemeh; Esmaeilian, Nasrin; Dehghani, Mohsen; Khatibi, Ali (Frontiers in Psychology, 2020)
Purpose: Family caregivers’ responses to patients’ pain behaviors have an important role in how patients perceive their pain condition. The current study investigated the mediating role of pain catastrophizing on the link between perceived caregiver responses and patient pain behaviors. Materials and methods: The sample of this cross-sectional study consisted of 200 patients with chronic pain (mean of age = 44.6; 71.5% were females). Participants responded to measures assessing their perception of their caregiver responses to their pain, their pain catastrophizing thoughts, and their pain behaviors. Results: The mediation analyses showed that perceived distracting responses were related to lower levels of catastrophizing thoughts in patients, which in turn was related to expressing more pain behaviors. Besides, perceived caregiver negative responses were related to higher levels of catastrophizing thoughts, which in turn was related to expressing more pain behaviors. Conclusions: Patients’ perceptions regarding how their caregiver respond to their pain condition can be related to their thoughts about their pain and how they react to their pain situation. Investigate the external sources that might have an impact on patients’ reactions to their pain, especially when those external sources are family caregivers who, in most situations, are with the patients for a prolonged duration, is important.